Hydrogel loaded with cerium-manganese nanoparticles and nerve growth factor enhances spinal cord injury repair by modulating immune microenvironment and promoting neuronal regeneration - Zhaoyang Gong; Zhenhao Chen; Dachuan Li; Xiao Lu; Jianwei Wu; Hanqiu Sun; Ximeng Wang; Siyang Liu; Xinlei Xia; Feizhou Lu; Jianyuan Jiang; Chi Sun; et al. (Journal of Nanobiotechnology)
Abstract Background Spinal cord injury (SCI) treatment remains a formidable challenge, as current therapeutic approaches provide only marginal relief and fail to reverse the underlying tissue damage. This study aims to develop a novel composite material combining enzymatic nanoparticles and nerve growth factor (NGF) to modulate the immune microenvironment and enhance SCI repair. Methods CeMn nanoparticles (NP) and CeMn NP-polyethylene glycol (PEG) nanozymes were synthesized via sol–gel reaction and DSPE-mPEG modification. Transmission Electron Microscopy, Selected-Area Electron Diffraction, X-ray Diffraction and X-ray Photoelectron Spectroscopy confirmed their crystalline structure, mixed-valence states, and redox properties. Size uniformity, biocompatibility, and catalytic activity were assessed via hydrodynamic diameter, zeta potential, and elemental analysis. The Lightgel/NGF/CeMn NP-PEG composite was synthesized and characterized via electron microscopy, compression testing, rheological analysis, NGF release kinetics, and 30-day degradation studies. Both in vitro and in vivo experiments were conducted to evaluate the therapeutic effects of the composite on SCI. Results The Lightgel/NGF/CeMn NP-PEG composite was successfully synthesized, exhibiting favorable physical properties. At a CeMn NP-PEG concentration of 4 µg/mL, the composite maintained cell viability and demonstrated enhanced biological activity. It also showed superior mechanical properties and an effective NGF release profile. Notably, the composite significantly upregulated the expression of nerve growth-associated proteins, reduced inflammatory cytokines, scavenged reactive oxygen species (ROS), and promoted M2 macrophage polarization by inhibiting the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway. In a rat SCI model, it facilitated functional recovery and attenuated inflammation. Conclusion The Lightgel/NGF/CeMn NP-PEG composite shows significant therapeutic promise for SCI, effectively eliminating ROS, promoting M2 macrophage polarization, reducing pro-inflammatory cytokines, and supporting neuronal regeneration. These effects substantially enhance motor function in SCI rats, positioning it as a promising candidate for future clinical applications. Graphical Abstract